2022
DOI: 10.3389/fenrg.2022.820330
|View full text |Cite
|
Sign up to set email alerts
|

Ulmus davidiana var. japonica Extracts Suppress Lipopolysaccharide-Induced Apoptosis Through Intracellular Calcium Modulation in U937 Macrophages

Abstract: This study was aimed to examine the antiapoptotic effect of Ulmus davidiana extracts through regulation of the intracellular cation mobilization in U937 human monocytic cells. To investigate the modulatory effects on lipopolysaccharide-induced apoptosis and the Ca2+ signaling pathway, we measured the levels of intracellular Ca2+ and various protein markers such as Bax, Bcl-2, and PARP. To isolate biopotent molecules, the branches of U. davidiana were processed sequentially using 60% ethanol, supercritical flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 86 publications
(70 reference statements)
2
0
0
Order By: Relevance
“…Next, we tried to find out which compound in U60E plays this role. In a previous study, we confirmed that C7A ( Supplementary Figure 2 ) is an important bioactive compound related to cell survival isolated from U. davidiana extract, and U60E also contains abundant C7A( 24 ). Therefore, we hypothesized that C7A contained in U60E is an important compound in preventing the decrease in cell viability of pericytes.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Next, we tried to find out which compound in U60E plays this role. In a previous study, we confirmed that C7A ( Supplementary Figure 2 ) is an important bioactive compound related to cell survival isolated from U. davidiana extract, and U60E also contains abundant C7A( 24 ). Therefore, we hypothesized that C7A contained in U60E is an important compound in preventing the decrease in cell viability of pericytes.…”
Section: Resultssupporting
confidence: 74%
“…U. davidiana extract also prevents apoptosis in various cells, such as mouse embryonic fibroblast cells, mouse embryonic liver cells, and rat pheochromocytoma cells [10–12]. In addition, in a previous study, we confirmed that the C7A compound contained in U. davidiana extract had bioactivity related to cell survival, and U60E also contained C7A ( 24 ). In addition, C7A is known as a representative bioactive compound of U. davidiana extract ( 22 , 23 ).…”
Section: Discussionsupporting
confidence: 71%
“…Macrophages respond to pathogens and cause an inflammatory response, producing pro-inflammatory cytokines such as TNF-α, IL-6, and IL-1β. In addition, inflammatory factors such as NO produced by iNOS and PGE2 produced by COX-2 are also secreted [68,69].…”
Section: Identification Of Inflammatory Genes Using Rt-pcrmentioning
confidence: 99%